THE EFFECT OF FRENCH ON ENGLISH - Isaqova Shoxidaxon (International Engineering Journal For Research & Development, 2020)
The article describes the influence of the French language on the English language over the years and the number of French words in the English dictionary today, as well as morphological and semantic changes in the words.